Local and Systemic Antibody Responses in Beef Calves Vaccinated with a Modified-Live Virus Bovine Respiratory Syncytial Virus (BRSV) Vaccine at Birth following BRSV Infection - David A. Martínez; Manuel F. Chamorro; Thomas Passler; Laura Huber; Paul H. Walz; Merrilee Thoresen; Gage Raithel; Scott Silvis; Ricardo Stockler; Amelia R. Woolums (Veterinary Sciences, 2022)
Maternal antibodies interfere with BRSV vaccine responses and efficacy in young calves. The objective of this study was to determine if vaccination before the complete absorption of colostral antibodies results in adequate immune priming and clinical protection of beef calves. Within 6 h of life, calves were randomly assigned to 2 different treatment groups. Group Vacc (n = 25) received a single dose of a modified-live virus (MLV) BRSV vaccine intranasally (IN) and group Control (n = 25) received 2 mL of 0.9% saline IN. At approximately 3 months of age, all calves were experimentally challenged with BRSV. Serum and nasal secretion samples were collected before and after challenge for BRSV real-time RT-PCR and antibody testing. Respiratory signs were not observed before challenge. After challenge, respiratory scores were similar between groups. On the challenge day, >40% of calves in each group were febrile. The mean serum and nasal BRSV-specific antibody titers indicated natural BRSV exposure before the experimental challenge in both groups. All calves tested positive for BRSV and had a similar duration of shedding after challenge. Based on these results, vaccination at birth does not offer advantages for immune priming or clinical protection for beef calves in BRSV-endemic cow-calf herds.